Securitization under Asymmetric Information over the Business Cycle - Martin Kuncl (Bank of Canada, 2015)
This paper studies the efficiency of financial intermediation through securitization in a model with heterogeneous investment projects and asymmetric information about the quality of securitized assets. I show that when retaining part of the risk, the issuer of securitized assets may credibly signal its quality. However, in the boom stage of the business cycle this practice is inefficient, information on asset quality remains private, and lower-quality assets accumulate on balance sheets of financial intermediaries. This prolongs and deepens a subsequent recession with an intensity proportional to the length of the preceding boom. In recessions, the model also produces amplification of adverse selection problems on resale markets for securitized assets. These are especially severe after a prolonged boom period and when securitized high-quality assets are no longer traded. The model also suggests that improperly designed regulation requiring higher explicit risk retention may become counterproductive due to a negative general-equilibrium effect; i.e., it may adversely affect both the quantity and the quality of investment in the economy.
Keywords: E32; E44; G20; 330; Business fluctuations and cycles; Credit and credit aggregates; Economic models; Financial markets; Financial stability; Financial system regulation and policies